Emosi dan Hubungan Antar Sebaya pada Anak Tunalaras Usia Sekolah antara Terapi Musik Klasik (Mozart) dan Murrotal (Surah Ar-Rahman) - Padila Padila; Setiawati Setiawati; Iin Inayah; Henny Suzana Mediani; Chatarina Suryaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to analyze the differences in the effectiveness of traditional music therapy (Mozart) and murrotal therapy (surah ar-Rahman) on emotional changes and peer relationships in school-aged children in SDN 1 Noman Musi Rawas Utara. The design of this study uses a quasi-experimental, pre-test, and post-test design. The results of the survey, there are differences in traditional music therapy (Mozart) and murrotal (ar-Rahman) on emotional changes and peer relationships in children with disabilities. There was a significant difference in the mean tunalaras after being given the classic intervention (Mozart) week 5, which was 9.06. In contrast, after being given the murrotal intervention (Ar-Rahman) week 5, it fell to 2.24. the mean difference in the score of tunalaras was 6.82 times, Conclusions, Murrotal therapy (Ar-Rahman) 6-7 times faster to reduce emotionally and improve peer relations in children with tunalaras compared to traditional music therapy (Mozart). Keywords: Tunalaras Children, Murrotal (Surah Ar-Rahman), Classical Music (Mozart)